When Can Inverted Water Tables Occur Beneath Streams? - Xie, Yueqing; Cook, Peter G; Brunner, Philip; Irvine, Dylan J; Simmons, Craig T (My University, 2014)
Decline in regional water tables (RWT) can cause losing streams to disconnect from underlying aquifers. When this occurs, an inverted water table (IWT) will develop beneath the stream, and an unsaturated zone will be present between the IWT and the RWT. The IWT marks the base of the saturated zone beneath the stream. Although a few prior studies have suggested the likelihood of an IWT without a clogging layer, most of them have assumed that a low-permeability streambed is required to reduce infiltration from surface water to groundwater, and that the IWT only occurs at the bottom of the low-permeability layer. In this study, we use numerical simulations to show that the development of an IWT beneath an unclogged stream is theoretically possible under steady-state conditions. For a stream width of 1 m above a homogeneous and isotropic sand aquifer with a 47 m deep RWT (measured in an observation point 20 m away from the center of the stream), an IWT will occur provided that the stream depth is less than a critical value of 4.1 m. This critical stream depth is the maximum water depth in the stream to maintain the occurrence of an IWT. The critical stream depth decreases with stream width. For a stream width of 6 m, the critical stream depth is only 1 mm. Thus while theoretically possible, an IWT is unlikely to occur at steady state without a clogging layer, unless a stream is very narrow or shallow and the RWT is very deep.